2023
DOI: 10.3390/horticulturae9050521
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Biochar Suspension Mediated Alterations in Yield and Juice Quality of Kinnow (Citrus reticulata L.)

Abstract: Nutrient deficiency negatively affects the yield and quality of citrus fruit. The present experiment was carried out to investigate the improvement in fruit yield and juice quality of Kinnow (Citrus reticulata L.) by foliar application of nano-biochar suspension (NBS). The experiment was carried out in a citrus farmer’s orchard with a history of low fruit yield, using a randomized complete block design. Four NBS treatments, i.e., 0% (control), 1, 3, and 5%, were applied through foliar application at the flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The key characteristic of widely used nanoparticles is their size (ranges from 1 to 100 nm) owing to which they can easily diffuse through small membrane channels made up of proteins and lipids [ 32 ]. Several studies reported that the application of nanoparticles favored various crops, that is, the quality of citrus fruit juice [ 33 ], cucumber, tomato, mustard, Arabidopsis and maize crops to adapt under different environmental conditions [ 34 ] depending on plant species, its age and the concentration of metal nanoparticles [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The key characteristic of widely used nanoparticles is their size (ranges from 1 to 100 nm) owing to which they can easily diffuse through small membrane channels made up of proteins and lipids [ 32 ]. Several studies reported that the application of nanoparticles favored various crops, that is, the quality of citrus fruit juice [ 33 ], cucumber, tomato, mustard, Arabidopsis and maize crops to adapt under different environmental conditions [ 34 ] depending on plant species, its age and the concentration of metal nanoparticles [ 35 ].…”
Section: Discussionmentioning
confidence: 99%